Spatial and temporal variations of Cr in Jiaozhou Bay 1990. Issue 4 (February 2019) - Yang, Dongfang; Lin, Dong; Li, Ye; Wang, Qi; Li, Haixia
Abstract: Using investigation on Cd in May and August, 1990, this paper analyzed the spatial and temporal variations of Cd contents in Jiaozhou Bay. Results showed that in May, 1990, Cd contents in surface waters and bottom waters were 0.35-1.02 μg L -1 and 0.11-0.35 μg L -1, compared to 0.22-1.26 μg L -1 and 0.18-0.48 μg L -1 in August, 1990. The pollution level of Cd in this bay in 1990 was still slight. Cd contents were confirmed to Grade I and Grade II, and the pollution level of Cd in this bay in 1990 was still slight. Cd contents in both surface and bottom waters were in order of spring < summer. By means of vertical water's effect and horizontal water's effect, the sediment of Cd was rapid and continuous, resulting in accumulation effect or dilution effect in bottom waters. Cd contents in bottom waters were relatively high/low in case of Cd contents in surface waters were relatively high/low. Ocean is a large solution, all of the substances to be homogeneous no matter the source input is strong or weak. Ocean has the feature of homogeneity, which was demonstrated by a block diagram model.